Digitization and Materiality: Researching Community Memory Practice Today. (February 2015) - MacDonald, Richard L.; Couldry, Nick; Dickens, Luke
Among the most deep-seated anxieties of the Internet age is the fear of technologically produced forgetting. Technology critics and sociologists of memory alike argue that daily exposure to overwhelming flows of information is undermining our ability to connect and synthesize past and present. Acknowledging the salience of these concerns our approach seeks to understand the contemporary conditions of collective memory practice in relation to processes of digitization. We do so by developing an analysis of how digital technologies (image and audio capture, storage, editing, reproduction, distribution and exhibition) have become embedded in wider memory practices of storytelling and commemoration in a community setting: the Salford Lads Club, an organization in the north of England in continuous operation since 1903. The diverse memory practices prompted by the 100th anniversary of the Club's annual camp provide a context in which to explore the transformations of access, interpretation and use, that occur when the archives of civic organizations are digitized. Returning to Halbwachs' (1992) seminal insight that all collective memory requires a material social framework, we argue, contrary to prevailing characterizations of digitization, that under specific conditions, digital resources facilitate new forms of materialization that contribute to sustaining a civic organization's intergenerational continuity.